Advanced Assistance in Scientific Manuscript Preparation Using Artificial Intelligence (AI), Google Scholar, and Reference Management Tools to Strengthen Students’ Academic Literacy and Publication - Moch. Amrodji; Agung Hariadi; Hendrik Richard; Tries Edy Wahyono (Universitas Kristen Cipta Wacana, 2026)
This community service program aimed to strengthen students’ academic literacy and improve the quality of scientific publications through advanced assistance in scientific manuscript preparation using Artificial Intelligence (AI), Google Scholar, and reference management tools. The activity involved undergraduate students and was conducted through training sessions, guided practice, and intensive mentoring focused on literature searching, citation management, academic paraphrasing, and manuscript organization. AI-based tools were introduced to support idea development, language refinement, and academic writing efficiency while maintaining research ethics and originality. The implementation results indicated increased student understanding of scientific writing techniques, improved ability to manage references systematically, and higher confidence in preparing publication-oriented manuscripts. Participants were also able to utilize digital academic resources more effectively in supporting evidence-based writing. Overall, the program contributed positively to enhancing students’ academic competencies and fostering a sustainable culture of scholarly writing in higher education.